A meta-analysis of the efficacy of physical exercise interventions on activities of daily living in patients with Alzheimer's disease - Xiao, Yang; Fan, Yu; Feng, Zhengteng (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to systematically review published randomized controlled trials on the effects of physical exercise on activities of daily living (ADL) in Alzheimer's patients through meta-analysis, thereby synthesizing existing evidence to provide scientific intervention recommendations for exercise prescriptions in Alzheimer's patients.MethodsBased on strict literature inclusion and exclusion criteria, a systematic search was conducted in databases including PubMed and Web of Science from their inception to July 1, 2024. The Cochrane risk assessment tool was used to evaluate the design of randomized controlled trials. Studies reporting on physical exercise interventions for ADL in Alzheimer's patients were systematically identified. Subgroup analyses and meta-regression were performed to explore sources of heterogeneity.ResultsNineteen articles, for analysis, providing 27 randomized controlled trials (RCTs). A random-effects model was used to calculate the effect size and 95% confidence interval for each independent study, and meta-analysis was performed using Stata 16.0 and RevMan 5.4 software. The results showed that physical exercise might significantly improve ADL in Alzheimer's patients (SMD = 0.33, 95% CI: 0.12–0.54, I2 = 81.7%). Sensitivity analysis confirmed the robustness of the results (p > 0.05). Egger's test did not reveal significant publication bias (p = 0.145). Samples were divided into different subgroups based on intervention content, duration, frequency, and session length. Subgroup analysis based on intervention characteristics showed that resistance training or aerobic exercise (SMD = 0.83, 95% CI: 0.60–1.05), long-term interventions (>6 months, SMD = 0.31, 95% CI: 0.13–0.49), medium-frequency interventions (4-5 times per week, SMD=0.39, 95% CI: 0.23-0.55), and short-duration training ( ≤ 30 min, SMD = 0.96, 95% CI: 0.71–1.21) might be most effective in enhancing ADL in Alzheimer's patients. These improvements were not only statistically significant but also had substantial impact in clinical practice.ConclusionResistance training or aerobic exercise lasting more than 6 months, 4–5 times per week, and lasting no more than 30 min per session may be most effective in improving ADLs in patients with Alzheimer's disease.